Aggregate production functions and the accounting identity critique: Further reflections on Temple's criticisms and misunderstandings - Jesus Felipe; John McCombie (Levy Economics Institute of Bard College, 2012)
In a reply to Felipe and McCombie (2010a), Temple (2010) has largely ignored the main arguments that underlie the accounting identity critique of the estimation of production functions using value data. This criticism suggests that estimates of the parameters of aggregate production functions cannot be regarded as reflecting the underlying technology of the industry. While Temple concedes some points, he erroneously believes that the critique holds only under some ad hoc assumptions. As a consequence, he argues that the critique works only part-time. This rejoinder discusses Temple's arguments and demonstrates that the critique works full-time.
Keywords: C43; O11; O16; O47; O53; 330; Accounting Identity; Aggregate Production Function; Aggregation Problems; Value-added Identity; Value Data